2022
DOI: 10.1007/s10071-022-01667-9
|View full text |Cite
|
Sign up to set email alerts
|

Horses form cross-modal representations of adults and children

Abstract: Recently, research on domestic mammals' sociocognitive skills toward humans has been prolific, allowing us to better understand the human-animal relationship. For example, horses have been shown to distinguish human beings on the basis of photographs and voices and to have cross-modal mental representations of individual humans and human emotions. This leads to questions such as the extent to which horses can differentiate human attributes such as age. Here, we tested whether horses discriminate human adults f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The signi cant number of horses whose rst look toward the incongruent video was longer than their rst look toward the congruent video is consistent with the ndings of previous cross-modal experiments in horses (Nakamura et al 2018;Trösch et al 2019a;Jardat et al 2023). In other words, horses' rst look toward the videos was preferentially directed toward the video that did not correspond to the sound heard.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The signi cant number of horses whose rst look toward the incongruent video was longer than their rst look toward the congruent video is consistent with the ndings of previous cross-modal experiments in horses (Nakamura et al 2018;Trösch et al 2019a;Jardat et al 2023). In other words, horses' rst look toward the videos was preferentially directed toward the video that did not correspond to the sound heard.…”
Section: Discussionsupporting
confidence: 89%
“…The experimental setup was similar to that used to investigate cross-modal recognition of human anger and joy by horses as well as cross-modal recognition of adults and children (Trösch et al 2019a;Jardat et al 2023). A horse was placed in the middle of the stall and attached with two loose ropes.…”
Section: Methodsmentioning
confidence: 99%
“…African bush elephants (Loxodonta africana) use auditory cues to differentiate men, who pose a significant hunting threat, from boys, who do not and show more defensive bunching and investigative sniffing after playbacks of men's voices [59]. Domestic horses (Equus ferus caballus) use both auditory and visual cues to differentiate adults from children and show increased heart rates during children's vocalizations [60]. However, Koda and Shimoju [33] found that dogs behaved in a similar way toward unfamiliar women (from 20 to 40 years old) and unfamiliar girls (from 8 to 13 years old); they did not include a comparison of unfamiliar men and unfamiliar boys in their study.…”
Section: Limitationsmentioning
confidence: 99%
“…See the recent review by Brubaker and Udell [ 22 ]. For example, there have been studies of animal models of depression [ 23 ], emotion [ 24 ], sensory sensitivity and temperament [ 25 ], cross-modal representation [ 26 , 27 ], auditory and other sensory processing [ 28 ], exploratory behavior [ 29 ], and social cognition [ 30 , 31 , 32 , 33 ]. Focusing on visual cognition, the topics cover face recognition [ 34 ], long-term memory [ 35 ], visual laterality and possible hemispheric asymmetry [ 36 , 37 ], and interocular transfer [ 38 ].…”
Section: Introductionmentioning
confidence: 99%